Key Trends in The Development of Renewable Energy - Kristina Gerasimovna TSARITOVA; Tatyana Mikhailovna SHPILINA; Petr Viktorovich SOLODUHA (Communications of International Proceedings, 2021)
Renewable energy sources (RES) are becoming increasingly widely used in different countries. The progress made in recent decades in the development of technologies for the efficient use of renewable energy has led to a public understanding that without the use of solar energy, wind energy, biomass energy and other almost universally available and environmentally friendly natural renewable energy sources, it will be difficult to ensure long-term effective, sustainable and safe energy development of mankind. The article discusses the key trends in the development of alternative energy in the world. The main factors contributing to the growth of investments in renewable energy sources are analyzed, and the prospects for the development of alternative energy in Russia are assessed.
Keywords: Renewable Energy; Alternative Energy; Solar Energy; Green Economy.